NEW POLYMERIC AMPHIPHILES OF COMPLICATED ARCHITECTURE: FROM THE SYNTHESIS OF PRIMARY OLIGOMER ELEMENTS TO THEIR ASSEMBLY INTO POLYMERIC SURFACTANTS WITH A BLOCK AND COMB-LIKE STRUCTURE - Zaichenko, Oleksandr (Collection of scientific papers «ΛΌГOΣ», 2023)
The routes of tailored synthesis and properties of novel polymeric surfactants and derived supramolecular structures, micelles, intermolecular complexes and nanoparticles, of desired size, morphology and functionality are developed. Combined radical and non-radical methods of the synthesis of primary building blocks containing end or side reactive groups and their using for controlled assemblage of polymeric surfactants of block- and/or branched architectures were developed.